Redistributive authoritarianism: land reform and regime durability in the Middle East - Hartnett, AS (2019)
A growing literature on land reform under autocracy shows that leaders often use the expropriation and redistribution to disempower incumbent elites and to signal a credible commitment to potential coalition members. Although these strategies have been found to extend leader tenure in Latin America (Albertus and Menaldo, 2012), these patterns have yet to be systematically tested in other parts of the world. Counter to the expectations generated by the Latin American experience, I find that leaders who pursue land reform in the Middle East and North Africa (MENA) have shorter tenures than non-reformers. This finding motivates my central research question: why are redistributive autocrats less likely to endure than their non-redistributive counterparts? I address this puzzle in two stages. First, I argue that the legacies of European colonialism impacted the inclusivity of elite coalitions. In countries with legacies of exclusive coalitions, autocrats inherited more intense demands for redistribution than in countries with legacies of inclusive coalitions. Strong demands from previously excluded elites drove leaders to pursue radical land reforms. I use a medium-N quantitative analysis to uncover patterns regarding the implementation of land reform and the survival prospects of redistributive autocrats. Second, radical reformers must also decide how to attract a loyal support coalition after redistribution is underway. Radical reformers who simultaneously extend cooptive state capacity through investment in and provision of “soft” institutions (e.g., agricultural cooperatives, health, education) are more likely to send a credible signal to potential members of an expanded supporting coalition. Alternatively, autocrats that pursue radical reform and rely on the expansion of repressive institutions (e.g., the military) are less likely to attract new supporters and are consequently more vulnerable to ouster. I turn to the case studies of Jordan, Iraq, and Egypt to disentangle the patterns suggested by the cross-national findings.